Analysis of the Nature of Learning and Instruction in Elementary Schools Through a Literature Study - Clara Noviantri Halawa; Fitri Sibarani; Amanda Daniela Naibaho; Chindy Abelia Nasution; Rahmilawati Ritonga (AMK : Abdi Masyarakat UIKA, 2026)
This study aims to comprehensively analyze the nature of learning and instruction in elementary schools through a literature study approach. The review was conducted by examining various classical and modern learning theories, concepts of 21st-century learning, and the practical implications that emerge within the context of basic education. The data were obtained from academic books, national and international scientific journals, research reports, and various digital publications relevant to the topic. Based on the literature review, learning is understood as a complex process that results in changes in behavior, knowledge, skills, values, and attitudes through direct experience or social interaction. Effective instruction requires a paradigm shift from teacher-centered learning to student-centered learning, where teachers are no longer merely transmitters of information but act as facilitators, motivators, and guides in the learning process. The study also shows that the implementation of 21st-century learning in elementary schools demands the application of instructional strategies that stimulate critical thinking, creativity, collaboration, and digital literacy. Learning must be designed to accommodate the developmental needs of children, particularly because elementary students are at the concrete operational stage, requiring real and contextual learning experiences. This study emphasizes that instructional quality will improve when planning, implementation, and evaluation are developed based on a deep understanding of children’s learning characteristics. Thus, this literature study provides a comprehensive overview of the importance of understanding the nature of learning and instruction as the foundation for developing effective, relevant, and sustainable educational practices in elementary